The chemokines CXCL10 and XCL1 recruit human annulus fibrosus cells - Hegewald, Aldemar Andres; Schmieder, Kirsten (Spine, 2012)
Study Design. Human annulus fibrosus tissue and cells were analyzed for the presence of chemokine receptors and the migratory effect of selected chemokines. Objective. To investigate spontaneous repair mechanisms and underlying cell recruitment in response to annular tears and degenerative defects. Summary of Background Data. Resorption of herniated disc tissue and the attempt to close annulus tears with repair tissue occur spontaneously. Although chemokines are suggested to play a role in resorption of herniated disc tissue, the role of chemokines in annulus fibrosus homeostasis and repair remains unclear. Methods. Cells were isolated from annulus fibrosus tissue and expanded in the presence of human serum. Multiwell chemotaxis assays were used to analyze the migratory effect of human serum and 0 to 1000 nM concentrations of the chemokines CXCL7, CXCL10, CXCL12, CCL25, and XCL1 on annulus fibrosus cells (AFCs) (n = 9 per chemokine and dose). Presence of corresponding chemokine receptors in AFCs was determined by real-time polymerase chain reaction analysis and immunohistochemistry. Results. Serum (0.1%-10%) significantly (P < 0.01) stimulates the migration of AFCs. Compared with untreated cells, the migration of cells was significantly (P < 0.01) enhanced upon stimulation with 100 to 1000 nM CXCL10 and 1000 nM XCL1. Chemokine receptors showed low expression levels in expanded AFCs as assessed by polymerase chain reaction. Immunohistochemical staining of the CXCL10 receptor CXCR3 and the XCL1 receptor XCR1 showed that the presence of the particular receptors in AFCs expanded under conventional cell culture conditions. In native annulus fibrosus tissue, CXCR3 was evident, whereas XCR1 could not be detected. Conclusion. The findings suggest that chemokines, in particular CXCL10, effectively recruit isolated AFCs. This suggests that chemokines are involved in annulus fibrosus homeostasis and potentially in spontaneous annulus repair attempts. This might have important implications for biological annulus-sealing strategies.
Gesehen am 06.04.2018